An audio-visual resource to improve transparency in SAIL Databank’s data access process. - Roberts, Christopher (International Journal of Population Data Science, 2024)
Background Since 2007, SAIL Databank has been entrusted with anonymised health and administrative data for the population of Wales. This includes ~85% of primary and 100% secondary care health records, and a range of administrative data that includes education, employment, environment, housing, justice and social care data. This data is accessible to approved researchers who can demonstrate positive societal impact from its use. Introduction It has always been vital for SAIL Databank to build and maintain extremely high levels of trust amongst its stakeholders; data users, data providers and the public who are represented in the anonymised datasets. This trust has been earned through a robust range of technical, physical and procedural safeguards known as SAIL’s ‘privacy-by-design’. Public-facing information has been vital to maintain trust through transparency and manifests in SAIL’s data use register, publications register, and clear information offered via its website. This work represents the next evolution in SAIL’s commitment to transparency in creating an audio-visual representation of its data access process. Method Ensuring current available information on SAIL’s public facing website was clear and accessible through consultation with SAIL’s public involvement panel – The Consumer Panel. Streamlining and presenting this information based on Consumer Panel feedback. Maintaining SAIL’s commitment to Welsh language standards by translating this information. Consultation with colleagues and Swansea University procurement to identify a suitable creative agency to take forward the idea of a data access process animated video. Communicating requirements and providing briefing documents to the selected creative agency, Buffoon Media. Reviewing potential voiceovers for narration of animated video to ensure an accessible tone, pace and dual language delivery. Receipt of completed animated video placed alongside corresponding data access process text on SAIL’s website. Results Production of an audio-visual resource that improves transparency around SAIL’s data access process and compliments its existing process guidance. This resource is freely and publicly accessible via its website, including components such as: Accessible design colours, fonts and presentation in keeping with SAIL’s existing brand. Use of images, graphics and animation that bring the process to life. A professional and accessible voice-over audio explaining each element within the process. A bi-lingual voice-over that recognises Wales’ large number of Welsh language speakers. Resource can be found at: https://saildatabank.com/data/apply-to-work-with-the-data/ Conclusion Building on SAIL’s commitment to trust and transparency since inception its anticipated that this new video resource will improve transparency for all of SAIL’s stakeholders in understanding and engaging with SAIL’s data access process. References Jones KH, Ford DV, Jones C, Dsilva R, Thompson S, Brooks CJ, Heaven ML, Thayer DS, McNerney CL, Lyons RA. A case study of the Secure Anonymous Information Linkage (SAIL) Gateway: a privacy protecting remote access system for health related research and evaluation. Journal of Biomedical Informatics: special issue on medical data privacy 2014. Ford DV, Jones KH, Verplancke JP, Lyons RA, John G, Brown G, Brooks CJ, Thompson S, Bodger O, Couch T, Leake K. The SAIL Databank: building a national architecture for ehealth research and evaluation. BMC Health Services Research 2009;9:157 http://www.biomedcentral.com/1472-6963/9/157 Lyons RA, Jones KH, John G, Brooks CJ, Verplancke JP, Ford DV, Brown G, Leake K. The SAIL databank: linking multiple health and social care datasets. BMC Medical Informatics and Decision Making 2009; 9:3. http://www.biomedcentral.com/1472-6947/9/3 Rodgers, S.E., Demmler J., Dsilva R., Lyons R. Health and Place. 28 Sept 2011, Protecting health data privacy while using residence-based environment and demographic data. Health and Place doi: 10.1016/j.healthplace.2011.09.006 https://www.ncbi.nlm.nih.gov/pubmed/21996431 Rodgers SE, Lyons RA, Dsilva R, Jones KH, Brooks CJ, Ford DV, John G, Verplancke JP. Residential Anonymous Linking Fields (RALFs): a novel information infrastructure to study the interaction between the environment and individuals' health. Journal of Public Health (Oxf). Dec 31 (4): 582-588, 2009.